Die populärkulturelle Rezeption der Schlacht bei den Thermopylen am Beispiel von Frank Millers „300“ im Vergleich mit historischen Quellen - Thomas Jenny (Historia.scribere)
In 1998, Frank Millers ";300";, a comic which processes the Battle of Thermopylae, a part of the Greco-Persian Wars, was released. Being published for entertaining purposes, parts of Millers comic nevertheless adhere surprisingly close to their historical example. This paper compares Frank Millers contemporary depiction of the Battle of Thermopylae to the descriptions provided by the Histories of Herodotus to emphasize major differences and similarities.